Students’ Perceptions of Teacher’s Written Feedback on Their Essays - Dwi Ratnasari (ELTE Journal (English Languange Teaching and Education), 2013)
AbstractThis paper discusses the perceptions that students had with regard to teacher’s written feedback on their essays. This study used descriptive method in gathering the data. The instrument utilized in the inquiry was survey questionnaire. The results of a survey given to a group of students at EnglishEducation Study Program, Faculty of Teacher Training and Education, Universitas PGRI Palembang show that the students believe that teacher’s written feedback is most useful in helping them improve their essays and that they willread the comments written for their essays carefully. The students also believe that both positive and negative comments encourage them to improve their essays.Many students prefer comments in the form of statement to comments in the form of question, but they also like comments in the form of imperative. Almost equalnumbers of students like the feedback from their writing teachers in the area of both language and content. The students prefer if the teacher marks every singleerror that they have made. Moreover, they like if the teacher corrects the errors on their essays.Key Words: perception, feedback, essay